1. The problem statement, all variables and given/known data Sorry, I don't know latex yet! The problem: -4/9(x^9)[(3/x^2)-(1/(2^1/3))] when x = 2^1/6. I'll put it in words too, cause that looks confusing. Negative four-ninths x to the ninth, times three over x squared minus one over the cube root of two, when x equals the sixth root of two. 2. Relevant equations x^9 = (2^1/6)^9 = 2^9/6 = 2^3/2 x^2 = (2^1/6)^2 = 2^2/6 = 2^1/3 Rationalizing the denominators for the second part of the equation, I get 3/x^2 = 3/2^1/3 = 3(2^2/3)/2 and 1/(2^1/3) = (2^2/3)/2 3. The attempt at a solution Now, when I put them all together I get -4/9(2^3/2)(2^2/3) = -4/9(2)(2^1/6) = -8/9(2^1/6). Now here's my problem, my book answers the problem as -16/9(2^1/6). I've done it over and over again, and still I get the -8/9. I have also had more than one wrong answer from the book, but this one I'm just not sure. All I want is someone else to work the problem and tell me whether I'm right or where I went wrong.